The Gut Microbiota Metabolite Urolithin B Improves Cognitive Deficits by Inhibiting Cyt C-Mediated Apoptosis and Promoting the Survival of Neurons Through the PI3K Pathway in Aging Mice - Chen, Peng; Chen, Fuchao; Lei, Jiexin; Wang, Gaohua; Zhou, Benhong (Frontiers in Pharmacology, 2021)
Background: Despite considerable advances in pharmacotherapy, more effective therapeutic interventions for aging-related neurodegenerative disorders (NDs), such as Alzheimer's disease (AD), remain limited. Urolithin B (UB), one of the major subcategories of urolithins (microbiota metabolites) found in various tissues after ellagitannin consumption, has been shown to possess antioxidant, anti-inflammatory, and antiapoptotic effects. However, the neuroprotective effect of UB on brain aging in mice and its potential mechanisms were still unknown. Methods: In the current research, we first assessed the ameliorative effects of UB on oxidative injury and apoptosis induced by H2O2 in neuro-2a cells. Then a subcutaneous injection of D-galactose in mice for 8 weeks was used to establish the aging model to evaluate the protective effects of UB. The capacity of memory and learning, alterations of hippocampus histology and corresponding molecular mechanisms were all evaluated. Results: The D-gal-induced accelerated aging model in vivo demonstrated that UB could significantly ameliorate deficits in learning and memory by inhibiting the accumulation of advanced glycation end products (AGEs) and elevating the expression and activity of Cu, Zn-SOD and CAT. Furthermore, UB downregulated the c-Jun N-terminal kinase (JNK) signaling pathway and prevented cytochrome c release from isolated mitochondria, thereby inhibiting neuronal apoptosis during the aging process. More importantly, UB stimulation of aging mice activated ERK and phosphoinositide 3-kinase (PI3K), leading to neuronal survival along with Akt and p44/42 mitogen-activated protein kinase (MAPK) phosphorylation and activation. Conclusion: In summary, UB effectively alleviated cognitive deficits and ameliorated brain aging-related conditions and could be considered a healthcare product to prevent aging-associated NDs such as AD.